Response of soil nitrogen components and its vertical distribution to rainfall redistribution during Robinia pseudoacacia forest restoration on the Loess Plateau - Ling Cao; Miaoping Xu; Yushu Liu; Zhouchang Yu; Lin Sun; Xingfang Tian; Ying Zhang; Jiayi Shi; Xinhui Han; Peizhi Yang; Wei Zhang (Ecological Indicators, 2023)
The effects of vegetation restoration on soil moisture dynamics and nutrient content have been widely studied; however, the knowledge on variation in rainfall redistribution and soil nitrogen component characteristics remain limited, particularly with respect to their relationship in restored ecosystems. Therefore, the characteristics of plant community structure, rainfall redistribution, and soil nitrogen components from farmland and Robinia pseudoacacia (RP) plantations of four restoration ages (12, 20, 30, and 45 a) were investigated and measured in the Wuliwan watershed in the Loess Plateau, China. The results showed that changes in plant community structure affected the rainfall redistribution processes. The throughfall and moisture entering the soil (MES) had the largest proportions (79.50 % and 60.25 %) in the initial and second distributions of atmospheric rainfall, respectively. With the increase in restoration age, the content of soil total nitrogen (STN), soil nitrate nitrogen (SNN), soil soluble total nitrogen (SSTN), soil soluble organic nitrogen (SSON), and soil soluble inorganic nitrogen (SSIN) all increased with restoration age in the upper soil (0–40 cm), fluctuated in the middle soil (40–100 cm), and increased and then decreased in the deeper soil (100–200 cm). In addition, the vegetation restoration process can indirectly affect soil nitrogen content and distribution patterns by affecting the rainfall redistribution process. In the upper soil, litter interception (LI) had a significant effect on STN by affecting SSIN and SSON. In the middle soil, both LI and MES had significant effects on STN through SSIN and SSON, respectively. In the deeper soil, LI had no significant effect on any nitrogen component, whereas MES had a significant effect on STN by affecting SSIN. Overall, this study indicates that RP plantation restoration has the potential to transform rainfall redistribution and soil nitrogen distribution, providing an important reference for the reciprocal feedback relationship between water and nitrogen.